Essential minerals and inorganic contaminants (barium, cadmium, lithium, lead and vanadium) in dried bee pollen produced in Rio Grande do Sul State, Brazil - SATTLER,José Augusto Gasparotto (2016)
Abstract Like other beehive products, such as honey, royal jelly and propolis, bee pollen has attracted great interest because of the health benefits it can provide when consumed. Bee pollen has high contents of sugars and proteins and a low content of lipids, it is also a rich source of vitamins and other bioactive compounds, which makes it an attractive micronutrient supplement. However, few studies have investigated its composition. Therefore, the aim of this study was to characterize the essential minerals and inorganic contaminants present in bee pollen produced at apiaries in Rio Grande do Sul State, Brazil. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) revealed the presence of 8 essential minerals (calcium, iron, copper, chromium, manganese, molybdenum, phosphorus and zinc) in the 5 analyzed samples; 6 of them were in sufficiently high amounts to meet dietary requirements. Of the 5 inorganic contaminants assessed (barium, cadmium, lithium, lead and vanadium), only cadmium was present at levels over the International Honey Commission’s standards. All bee pollen samples showed a high content of the 8 essential minerals. Contamination usually results from the use of pesticides, fertilizers and other chemicals in agriculture; thus, monitoring of its levels must be included in bee pollen analysis.